Walls and bridges : social justice and public policy - Cortese, Anthony Joseph Paul (SUNY series in public policy., 2003)
"This useful classroom resource for professors wishing to incorporate notions of justice into their courses examines a variety of America's most challenging social issues (education, poverty, hopelessness, crime, and health care), interwoven with racial and ethnic themes. Anthony J. Cortese illustrates how the tension between moral relativism on the one hand, and universal ethics on the other, makes concrete policy discussion difficult. He illustrates how, through a synthesis of justice, law, and power, a social ethics approach to public policy could resolve various intergroup conflicts and social problems. Included at the end of each chapter are "What You Can Do" exercises and activities that encourage students to apply what they have learned to their own lives."--Jacket